2017
DOI: 10.1007/s10803-017-3159-4
|View full text |Cite
|
Sign up to set email alerts
|

Differential Fairness Decisions and Brain Responses After Expressed Emotions of Others in Boys with Autism Spectrum Disorders

Abstract: Little is known about how emotions expressed by others influence social decisions and associated brain responses in autism spectrum disorders (ASD). We investigated the neural mechanisms underlying fairness decisions in response to explicitly expressed emotions of others in boys with ASD and typically developing (TD) boys. Participants with ASD adjusted their allocation behavior in response to the emotions but reacted less unfair than TD controls in response to happiness. We also found reduced brain responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 78 publications
1
4
0
Order By: Relevance
“…This finding is interesting given the mixed results in previous studies. For example, it is consistent with other studies employing neuroeconomics paradigms like the ultimatum game (Ikuse et al, 2018), dictator game (Klapwijk et al, 2017), or other resource allocation games (Tei et al, 2019), which found more prosocial behavior in ASD than in non-ASD participants of child, adolescent, and adult age (Paulus & Rosal-Grifoll, 2017). Moreover, research found that high-functioning ASD children judged the immoral behavior of an unknown peer more strictly (Li et al, 2014) and endorsed punishment of immoral behavior in a prisoner's dilemma game more often than NC (Li et al, 2018); which is in line with Baron-Cohen's (2005) conclusion that despite being rather self-focused, people scoring high on the autism spectrum have strong moral values, sense of justice, and think deeply about how to do good.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is interesting given the mixed results in previous studies. For example, it is consistent with other studies employing neuroeconomics paradigms like the ultimatum game (Ikuse et al, 2018), dictator game (Klapwijk et al, 2017), or other resource allocation games (Tei et al, 2019), which found more prosocial behavior in ASD than in non-ASD participants of child, adolescent, and adult age (Paulus & Rosal-Grifoll, 2017). Moreover, research found that high-functioning ASD children judged the immoral behavior of an unknown peer more strictly (Li et al, 2014) and endorsed punishment of immoral behavior in a prisoner's dilemma game more often than NC (Li et al, 2018); which is in line with Baron-Cohen's (2005) conclusion that despite being rather self-focused, people scoring high on the autism spectrum have strong moral values, sense of justice, and think deeply about how to do good.…”
Section: Discussionsupporting
confidence: 90%
“…However, in experimental settings, several studies have found that preschool autistic children do show helping behaviors (5,6). In resource allocation tasks [e.g., Dictator Game (DG) and Ultimatum Game (UG)], autistic children showed a higher preference for equality than self-interest compared to TD children (7)(8)(9)(10); but they tended to accept unfair offers (7,10). Different measures might identify different situation of prosocial behaviors, resource allocation tasks such as DG is believed to be powerful to illuminate individuals' social interactions because it could examine the extent to which individuals attain their own goals while simultaneously displaying altruistic behavior toward unrelated individuals.…”
Section: Introductionmentioning
confidence: 99%
“…These include, decreased loss-aversion and attraction effect on how subjective choices are evaluated (De Martino et al, 2008; Farmer et al, 2017), a tendency towards risk-seeking when the environment demands it (Gosling & Moutier, 2018) and how (little) alternative cues that usually elicit strong expectations (e.g. facial traits and emotions) impact decision-making in autism (Damiano et al, 2012; Hooper et al, 2019; Klapwijk et al, 2017). In these cases, the priors are default options that can be re-evaluated on the basis of changed circumstances or contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Eleven papers (40.7% of all value-based studies) investigated how value-based decisions change when choice-options are presented with decision frames, e.g., distinct emphases or with a third choiceirrelevant option. These papers consistently found that framing effects were less pronounced in autistic than in comparison participants (De Martino et al, 2008;Farmer et al, 2017;Hooper et al, 2019;Klapwijk et al, 2017;Panasiti et al, 2016;Shah et al, 2016;Fujino et al, 2017;Fujino et al, 2019;Fujino et al, 2020;Bellamy et al, 2021). However, Fujino et al (2017) found, in an economic decision-making paradigm with ambiguous and risky contexts, that autistic participants were less sensitive to context change in the ambiguous condition, compared to comparison participants (with no differences in the risky condition, similar to Gosling et al, 2018).…”
Section: Framing Studiesmentioning
confidence: 94%